2022
DOI: 10.1002/jcla.24407
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐binding proteins in diabetic microangiopathy

Abstract: Dynamic RNPs (ribonucleoprotein particles) are formed when RNAbinding proteins assemble with RNA. RNP compositions vary depending on the maturation or the functional state of the RNA as well as the cell environment. [1][2][3] All aspects of RNA life, including splicing, transcription, intracellular trafficking, modification, translation, as well as decay, are regulated by RBPs. In turn, RNA can modulate the location or activity of RBPs through a process called "riboregulation." 4 The PRK (protein kinase R) ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…RBPs are involved in complex interrelated molecular mechanisms of PDR, suggesting their potential as therapeutic targets for PDR 27 . Overexpression of the RBP lin-28 homolog B could exacerbate angiogenesis and elevate the protein levels of proangiogenic factors in human retinal endothelial cells and human retinal microvascular endothelial cells 28 .…”
Section: Discussionmentioning
confidence: 99%
“…RBPs are involved in complex interrelated molecular mechanisms of PDR, suggesting their potential as therapeutic targets for PDR 27 . Overexpression of the RBP lin-28 homolog B could exacerbate angiogenesis and elevate the protein levels of proangiogenic factors in human retinal endothelial cells and human retinal microvascular endothelial cells 28 .…”
Section: Discussionmentioning
confidence: 99%
“…With 20,500 proteins coding for genes by humans, they confirmed that 7.5% are linked to RNA metabolism through the binding and processing of RNA or forming significant parts of RNPs (Gerstberger et al, 2014). Cellular dysfunctions and human illnesses, such as neurological disease (Chen et al, 2021; Hao et al, 2016; Propson et al, 2021), immunodeficiency disease (Iritani, 2021), Parkinson's disease (Olsen & Feany, 2019), and cancer (Halbach et al, 2017), are linked to aberrant protein–nucleic acid interaction (Tu et al, 2022). Therefore, understanding the recognition mechanisms of protein–nucleic acids is critical to strengthen our knowledge of the complex pathogenic mechanisms (Valeur et al, 2017; Y.‐L.…”
Section: Introductionmentioning
confidence: 99%
“…illnesses, such as neurological disease (Chen et al, 2021;Hao et al, 2016;Propson et al, 2021), immunodeficiency disease (Iritani, 2021), Parkinson's disease (Olsen & Feany, 2019), and cancer (Halbach et al, 2017), are linked to aberrant protein-nucleic acid interaction (Tu et al, 2022). Therefore, understanding the recognition mechanisms of proteinnucleic acids is critical to strengthen our knowledge of the complex pathogenic mechanisms (Valeur et al, 2017;Wu et al, 2018;Yu et al, 2020).…”
mentioning
confidence: 99%